2019
DOI: 10.1073/pnas.1900985116
|View full text |Cite
|
Sign up to set email alerts
|

On the chain-melted phase of matter

Abstract: Various single elements form incommensurate crystal structures under pressure, where a zeolite-type “host” sublattice surrounds a “guest” sublattice comprising 1D chains of atoms. On “chain melting,” diffraction peaks from the guest sublattice vanish, while those from the host remain. Diffusion of the guest atoms is expected to be confined to the channels in the host sublattice, which suggests 1D melting. Here, we present atomistic simulations of potassium to investigate this phenomenon and demonstrate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…ML results were obtained from an ensemble of 16 models from which uncertainties have been estimated (shaded area). The results for form II in the bottom panels demonstrate the high transferability of the ML model which can accurately represent the overall lineshape of the unseen molecular crystal temperature [192], which exhibits a complex chain-melted phase that had previously not been characterized in detail. The MD simulations by Robinson et al were initialized in the expected ground-state phase for a given pressure at 200 K, and MD simulations in the NVT statistical ensemble were used to simulate phase transitions with temperature.…”
Section: Phase Diagram Predictionsmentioning
confidence: 87%
See 1 more Smart Citation
“…ML results were obtained from an ensemble of 16 models from which uncertainties have been estimated (shaded area). The results for form II in the bottom panels demonstrate the high transferability of the ML model which can accurately represent the overall lineshape of the unseen molecular crystal temperature [192], which exhibits a complex chain-melted phase that had previously not been characterized in detail. The MD simulations by Robinson et al were initialized in the expected ground-state phase for a given pressure at 200 K, and MD simulations in the NVT statistical ensemble were used to simulate phase transitions with temperature.…”
Section: Phase Diagram Predictionsmentioning
confidence: 87%
“…12 ML-based simulations for the exploration of phase diagrams of inorganic materials. a Temperature and pressure dependent phase diagram of potassium obtained from MD simulations using an ML potential [ 192 ]. Each point in the figure represents the result from an individual ML-based MD simulation in the NVT statistical ensemble.…”
Section: Applications To Industrymentioning
confidence: 99%
“…Here, we report on a novel 2D transition in a charge-ordered K-Sn alloy monolayer on Si(111), whereby the 'melting' of the charge order in the Sn host lattice is preceded and driven by a true 2D melting transition in the alkali sublattice. Sublattice melting is a well-known phenomenon in bulk ionic conductors where an ionic insulator acquires a highly conductive state when the sublattice containing the lighter ions, typically an alkali or Ag ion, melts while the heavier sublattice or 'host' lattice remains intact (13,14). A similar part-liquid part-crystalline state has been observed in thermoelectric compounds with strong chemical-bond hierarchy (15).…”
mentioning
confidence: 85%
“…Nature has provided us with many more types of phases than the elementary ones-solid, liquid, and gas-that we learn in school textbooks. Some of them can be rather exotic, such as the one considered in the PNAS article by Robinson et al (1), which deals with a remarkable but not so uncommon state of matter found in several elemental solids when they are compressed to gigapascal pressures (1 GPa = 10,000 bar). The solid in this specific case, elemental rubidium, crystallizes in a tetragonal structure composed of two interpenetrating lattices with incommensurate periodicity (Fig.…”
mentioning
confidence: 99%
“…Similarly, the intrachain loss of correlation indicates that the simulations may also offer a glimpse into the fundamental but elusive phenomenon of long-range correlations in 1D systems of particles. Both questions will benefit enormously from the availability of a computationally cheap yet realistic model of interaction between Rb atoms in phase III, such as the one developed by Robinson et al (1).…”
mentioning
confidence: 99%